(untitled) (Annals of Medical Research, 2021)
Aim: Regular physical activity is important to prevent damage and protect joint health in hemophilic individuals. However, hemophilia patients tend to limit their physical activity due to frequent bleeding. There may be some factors, such as fear of movement or kinesiophobia under these attitudes. For this reason, this study aimed to research the relationship between kinesiophobia and physical activity levels in adult hemophilic individuals.Material and Methods: This study was performed with a retrospective study design. A total of 44 patients included in this study; 33 were hemophilia A, 11 were hemophilia B. All hemophilic individuals were male and between the ages of 18-60 (mean=35.30±12.04). Tampa Scale for Kinesiophobia (TSK) was used to determine fear of movement. To determine the physical activity levels of individuals, the “International Physical Activity Questionnaire-Short Form” was used. The results were analyzed using Spearman correlation analysis and Mann-Whitney U test.Results: There was no statistical correlation between kinesiophobia degree and physical activity level (p=0.616, r=−0.081). There was also no significant difference in kinesiophobia scores between hemophilia A and hemophilia B (z=-0.707, p=0.479). High kinesiophobia levels (TSK score of ≥37) were present in 90.9% of patients. According to physical activity levels, 36.4 % of patients had low, 34.1 % had moderate and 29.5 % had high physical activity levels. Hemophilia A patients had higher physical activity levels than hemophilia B (z=-2.400, p=0.016). Conclusion: These results showed no correlation between physical activity level and kinesiophobia, but high kinesiophobia rates in adult hemophilic individuals. Hemophilia patients should be educated and encouraged about safe and fearless physical activity.